Terminación de las obligaciones contractuales en el código civil de ucrania - Anatoliy Kostruba (Ius Humani. Jornal do direito, 2019)
A contract is a means for self-organization and self-regulation of civil and legal relations between parties in the Civil Code of Ukraine. A distinguishing feature of a contractual obligation is the dependence of the beginning of a legal fact in its structure on the lawful will of a party (act) to a legal transaction or objective circumstance of reality (events). The objective of the paper is to study the mechanism of termination of obligations by determining the legal framework for its functioning. The specificity of legal facts of normative-compensating nature was determined by the use of normative and protective functions in the legislation. Civil property and its legal regulation of relations are aimed at achieving the legal result determined by their participants at the stage of the exercise of rights. The study reveals that the compensating effect of the legal termination mechanism is expressed at the stage of legal termination, which involves compensating the inability to correct a defect of a legal fact that hinders the achievement of a goal of legal regulation when exercising the right to the start of an anticipated legal effect according to a legal model of legal subjects accepted by the participants of the civil relations. The author dwells upon one of the forms of termination of contractual obligations, more specifically, on the beginning of cancellation and on the deferred status of a legal transaction.